Attenuated Total Reflection Fourier Transform Infrared (ATR‐FTIR) spectral discrimination of brain tumour severity from serum samples. Issue 3 (7th January 2014) - Hands, James R.; Dorling, Konrad M.; Abel, Peter; Ashton, Katherine M.; Brodbelt, Andrew; Davis, Charles; Dawson, Timothy; Jenkinson, Michael D.; Lea, Robert W.; Walker, Carol; Baker, Matthew J.
Abstract: Gliomas are the most frequent primary brain tumours in adults with over 9, 000 people diagnosed each year in the UK. A rapid, reagent‐free and cost‐effective diagnostic regime using serum spectroscopy would allow for rapid diagnostic results and for swift treatment planning and monitoring within the clinical environment. We report the use of ATR‐FTIR spectral data combined with a RBF‐SVM for the diagnosis of gliomas (high‐grade and low‐grade) from non‐cancer with sensitivities and specificities on average of 93.75 and 96.53% respectively. The proposed diagnostic regime has the ability to reduce mortality and morbidity rates. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)